2016
DOI: 10.1108/cpoib-08-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

Critiquing the marginalised place of research on women within international business

Abstract: Purpose This paper aims to provide a critical perspective of how the theme of women, and more broadly gender, have been treated in extant international business (IB) literature. It also suggests meaningful and promising avenues in this research space. Design/methodology/approach This paper is not intended to provide a comprehensive literature review; rather, it offers a critical and reflective view on the development of the IB stream of literature in which discussion of women has been largely marginalised. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…Recently, research interest has grown – concerning the importance of diversity management (DM) to promote women in management positions – to the point that it has become apanacea for every multinational corporation (MNC) that prides itself as being inclusive, diverse and global. Thus, a need exists to understand gender inequalities and DM in the context of MNCs from a critical perspective (Frenkel, 2017; Koveshnikov et al , 2019; Michailova and Hutchings, 2016). The present study responds to this call by adopting a decolonial feminist analysis of DM discourses of six women chief executive officers (CEOs) – working in MNCs in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research interest has grown – concerning the importance of diversity management (DM) to promote women in management positions – to the point that it has become apanacea for every multinational corporation (MNC) that prides itself as being inclusive, diverse and global. Thus, a need exists to understand gender inequalities and DM in the context of MNCs from a critical perspective (Frenkel, 2017; Koveshnikov et al , 2019; Michailova and Hutchings, 2016). The present study responds to this call by adopting a decolonial feminist analysis of DM discourses of six women chief executive officers (CEOs) – working in MNCs in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…As Sidani, Konrad and Karam [45] (p. 285) state it is 'the perceived importance of the impact of patriarchal family structures, the explicit favouring of males over females, and the assignment of women to nurturing roles within the private sphere of the family as the major limiting factors' to women's careers, more so than the absence of a legislative framework. However, Michailova and Hutchings [46] argue that women pursue careers in developing countries which lack the equality frameworks of their home nations because they perceive greater career advancement opportunities facilitated through international experience which is shown to increase career capital [47]. Furthermore, women in dual-career relationships may experience reduced financial remuneration in the form of allowances as their spouse receives the 'family benefits' (e.g., accommodation allowances), resulting in women's international work being devalued [2].…”
Section: Expatriate Women's Career Capital In a Middle Eastern Contextual Settingmentioning
confidence: 99%
“…This book chapter also highlighted the need for more research on women expatriates from developing economies, women expatriates working in non-business organisations, and women expatriates in non-traditional families. An article critiqued the marginalised place of women in international business (Michailova and Hutchings, 2016) and suggested that there had been little consideration given to women (or gender) within international business research and research on women expatriates has tended to focus on western women in business organisations. This article called for greater consideration of gender broadly in the field and specifically with reference to non-western contexts and the structures through which gender is enacted.…”
Section: Developing An Understanding Of Issues For Ntesan Overview Of...mentioning
confidence: 99%